Postural stability and fall risk in patients with obstructive sleep apnea: a cross-sectional study - Yilmaz Gokmen, Gulhan; GÜRSES, Hülya Nilgün; GÜRSES, HÜLYA NILGÜN; Zeren, Melih; ÖZYILMAZ, Semiramis; ÖZYILMAZ, SEMIRAMIS; Kansu, Abdullah; Akkoyunlu, Muhammed Emin (My University, 2021)
Purpose Nocturnal hypoxia and daytime sleepiness resulting from fragmented sleep may impair the ability of postural stability in subjects with OSA. This study investigates the effect of disease severity on postural stability and whether or not it poses a fall risk in individuals with obstructive sleep apnea (OSA).
Keywords: sleep apnea